Biofunctionalized tapered multimode fiber for dengue virus antibody detection - Mustapa, Mohd Azmir (2017)
The use of optical tapered fibers provides good sensitivity for the detection and measurement of biological and chemical compound especially biomolecules such as proteins, nucleic acids, antibodies, lipids, and carbohydrates. This thesis looks into the fabrication of a biofunctionalized tapered multimode fiber (TMMF) as a probe for anti-Dengue virus NS1 immunoglobulin G (anti-DENV NS1 IgG) detection. This device offers advantages by improving sensitivity, rapidness of detection, the size of device by making it more compact, and the field operability. In this research, TMMF was fabricated using a Vytran GPX-3000 glass processing system. A multimode fiber (MMF) with diameter of 125 μm is tapered until the size reduced to 10 μm with 10 mm of its waist length and transition length. The implemented technique is proved to induce some amount of light propagating outside the core of the tapered fiber and generates evanescent wave field (EWF) allowing high sensitivity to the changes in surrounding condition. The surface modification process onto TMMF involving three stages, namely silanization, activation with glutaraldehyde (GA), and immobilization of DENV NS1 glycoprotein on the surface of TMMF. This process is required to allow the interaction between inorganic silica TMMF and organic biomolecules. The silaned-TMMF treated with 3-amino-propyltriethoxysilane (APTES) and coated with 100 μg/mL of DENV NS1 glycoprotein specific to anti-DENV NS1 IgG antibodies in order to detect the presence of the antibodies. The generated EWF is applicable to measure the interaction between bound and unbound biomolecules on the surface by utilizing evanescent wave absorption (EWA) in the UV region. This biosensor device has the capability to detect the presence of anti-DENV NS1 IgG antibodies in a liquid sample in less than five minutes of incubation time. The concentration of the samples varies from 100 pg/mL until 1000 pg/mL with interval of 100 pg/mL. Results showed the sensitivity of the biofunctionalized TMMF to be 7×10-6 a.u./pg/mL with R-squared of 0.9938. The experiment done in this study demonstrates the potential of the biofunctionalized-TMMF to be developed and commercialized as a rapid and label-free sensor for dengue virus detection in the future.